Pengaruh Efektivitas Presensi Online Terhadap Disiplin Kerja Penyuluh Keluarga Berencana Di Perwakilan Bkkbn Provinsi Sulawesi Tengah - Wulandari; Mangngasing, Nasir; Erdiansyah (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2026)
This study aimed to examine the effect of online attendance effectiveness on the work discipline of Family Planning Extension Workers and to measure the magnitude of such effect. A quantitative approach with a survey method was employed. Online attendance effectiveness was measured using the DeLone & McLean (2003) model, encompassing six dimensions: system quality, information quality, service quality, use, user satisfaction, and net benefits, while work discipline was measured using the indicators proposed by Singodimedjo in Sutrisno (2023), comprising adherence to time regulations, institutional rules, behavioral norms, and other applicable regulations. Data were collected through a questionnaire distributed to 83 Family Planning Extension Worker respondents. Data analysis was conducted using simple linear regression, f-test, and the coefficient of determination (R²) with the aid of SPSS 27. The findings revealed that online attendance effectiveness had a positive and significant effect on the work discipline of Family Planning Extension Workers at the BKKBN Representative Office of Central Sulawesi Province, as evidenced by a f-value of 107,808 > t-table of 3,96. Online attendance effectiveness accounted for 57.1% of the variance in work discipline (R² = 0.571), while the remaining 42.9% was attributable to other factors outside the research model